Procesamiento de imágenes satelitales (2021)
Remote sensing is a technique that allows to observe and obtain digital, geographical information of objects at a distance, this system has elements such as sensor, reception center and distribution channel that allow to measure and make a perception work from sensors or radars, making it essential for using with satellite images whose purpose is to obtain information of different earth surface coverage. Landsat has a series of eight satellites mainly characterized by the observation of high-resolution images of the earth’s surface, there is passive and active remote sensing, a passive remote sensing system collects electromagnetic energy reflected by an observed object and coming from the earth’s surface, Through this system the present article exposes the Landsat satellite image processing methodology through Erdas Imagine and ArcGIS software in order to use different tools to determine coverage, as well as compare satellite imagens and software that allow obtain better results in the images.